NIETO BLANCO, Carlos: La religión contingente, Nobel, Oviedo, 2013. - Novella Suarez, Jorge Benito (Daimon Revista Internacional de Filosofia, 2015)
Reseña de NIETO BLANCO, Carlos: La religión contingente, Nobel, Oviedo, 2013.